Kompetensi SDM pada PT PAL Indonesia (Studi Literature Review) - Nabilah Maulidah Az-Zahroh; M. Isa Anshori (Politeknik Kampar, 2024)
HR competence is the ability and characteristics of a person in the form of knowledge, skills, and behavioral attitudes that are needed in carrying out the duties of his position in his work environment. Employee performance is the result of a person's work in quality and quality in accordance with predetermined standards based on the responsibilities given. The purpose of this study was to determine the competence of HR at PT PAL Indonesia. The method used in this research is a literature study conducted by searching the literature of books, articles, national journals. PT PAL Indonesia is committed to realizing quality human resources by improving employee competencies and abilities. Employee competency development is carried out in terms of improving the development of attitudes, knowledge, expertise, and skills in their respective fields. This is done with the aim of making PT PAL Indonesia's human resources as people who are able to work optimally with a calm and comfortable work environment, and produce good performance.